Analisis Faktor-faktor Adopsi Metode PsPSP pada Penanggulangan Hama Penggerek Buah Kakao (PBK) di Pekon Kuripan - Khairudin, Khairudin; Saty, Fadila Marga; Supriyatdi, Dedi (Jurnal Agro Industri Perkebunan, 2015)
PsPSP method is cultural technique of cacao cultivation for handling Cocoa Podborer (Conopomorpha cramerella Snell.), but less aplicated by farmers in Lampung Province. The research objective are investigated the adoption level and analyze influence factors toward PsPSP method of the cacao farmers adopted in Pekon Kuripan, Kecamatan Limau, Kabupaten Tanggamus. The research used survey method. Responder determined through randomized by taking 40 people of cocoa farmers. The research was carried out on October until November 2014. Scoring system is an instrument to analyze adoption level and Multiple Linier Regresion to analyse the influence factors of PsPSP method. Based on the result of interview used questioner known that the adoption level of cacao farmers are still less than average  value. Self inside factors (age, education level, cultivation experiences) and outside factor of farmer (elucidation intensity) are significant toward adoption level of PsPSP method. Wide area of farm and quantity of responsibility family are not significant toward adoption level of PsPSP method.Keywords : cocoa podborer, method adoption, PsPSPPermalink: http://jurnal.polinela.ac.id/index.php/AIP/article/view/17